A new species of Japanagromyza Sasakawa (Diptera: Agromyzidae) from the Brazilian Amazon with notes on biology - Monteiro, Nilton Juvencio Santiago; Carvalho-Filho, Fernando Da Silva; Esposito, Maria Cristina (Zootaxa, 2015)
Japanagromyza sasakawai sp. n. is described from the Brazilian Amazon, based on the male, female, third instar larva and puparium. This species is a leaf-miner of Terminalia catappa L. (Combretaceae), which is an introduced plant from the Old World tropics used in Brazil as an ornamental. The male aedeagus of J. sasakawai sp. n. differs from other species mainly in having the mesophallus covered with many spine-like processes. This is the third record of Japanagromyza Sasakawa in Brazil and first in the Brazilian Amazon. The key to Neotropical species of Japanagromyza by Sousa & Couri (2014) is modified to include this new species.